Information technology equipment management system (ITEMS) - monitoring module - Lapuz Lauren Lustria (2011)
IT equipment at UP Mindanao are indispensable tools that each department within the university has its own IT equipment designated to them. The unit responsible for maintaining these equipment is the university's Information technology Office (ITO). Not only does the ITO maintain the equipment, but it also offers some of its equipment for borrowing. Clients had to personally go to the office to avail the services. Furthermore, the request forms, which are the most important part of the transaction, eventually pile up and are difficult to organize and keep track of them all. This study developed a web=based system to address to these problems. Through the system, the clients are able to file a request, whether regarding the maintenance or borrowing of equipment, on-line. They are also able to view their request and the history of the equipment under their custody. The administrators are able to keep track of all the equipment under their supervision. They are also able to view the history of all the equipment, mange the requests of the clients, and be notified regarding the client's request.
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2011
Keywords: On-line automation; Information Technology Equipment Management System (ITEMS).; Monitoring module; Information Technology Office (ITO); ERP system; University of the Philippines Mindanao Integrated Information Management System (UPMIIMS); Rapid prototyping model..; Component-based development; Object-oriented paradigm; Graphical User Interface (GUI); ADOdb